KREATIVITAS GURU PAUD DI TAMAN KANAK-KANAK KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Chichi Ulfa Andela Ulfa Andela; Zulkifli N Zulkifli N2 '; Yeni Solfiah Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Creativity early childhood teachers at kindergarten in District of Peranap Indragiri Hulu Regency. The purpose of this study was to investigate the creativity possessed by early childhood teachers at kindergarten district of Peranap Indragiri Hulu Regency totaling 36 peoples. This empirically type of descriptive study consisting of a variable that is creativity. The study population of all early childhood teachers at kindergarten District of Peranap Indragiri Hulu Regency totaling 36 people.Based on the analysis of data using a percentage formula shows that early childhood teacher creativity in kindergarten District of PeranapIndragiri Hulu Regency obtained with 66.66% results in the category of "Good".Keywords: Creativity, Early Chilhood Teacher